World Hepatitis day 2021 -screening and vaccination against Hepatitis B virus in Accra, Ghana - Kwadwo Asamoah Kusi; William van der Puije; Diana A. Asandem; Rawdat Baba-Adam; Hardy Agbevey; Bright Asare; Philip Segbefia; Lutterodt Bentum-Ennin; Audrey Annan; Frank Osei; Doreen Teye-Adjei; Elsie Sutaya Galevo; et al. (BMC, 2023)
Abstract Background In Ghana, Hepatitis B virus (HBV) infection remains a major public health threat as in many parts of the world. Even with an effective vaccine, there are shortfalls with low vaccine coverage among adults. To create awareness and encourage vaccination, community engagement and public-private partnerships are needed in endemic settings to help fund campaigns and offer screening and vaccinations at no cost to under privileged people. Objectives An awareness and screening exercise was scheduled by University of Ghana-based Hepatitis-Malaria (HEPMAL) project team to coincide with the World Hepatitis Day (WHD) 2021. It was to engage the community in creating awareness of the menace and offer diagnostic services to ascertain prevalence levels and provide needed clinical support. Methods Participants from the University of Ghana community and its immediate environs were registered, taken through pre-counselling sessions where they were educated on hepatitis transmission and prevention before consenting. Eligible participants were screened for HBV markers (HBsAg, HBeAg, HBsAb, HBcAb,HbcAg) with a rapid test kit. All HBsAb-negative participants were recommended for initial vaccination at the event, whilst the subsequent shots were administered at the University Hospital Public Health Department. Hepatitis B surface Antigen-positive participants were counselled and referred for appropriate care. Results / Outcomes: A total of 297 people, comprising of 126 (42%) males and 171 (58%) females aged between 17 and 67 years were screened during the exercise. Amongst these, 246 (82.8%) showed no detectable protective antibodies against HBV and all of them agreed to and were given the first dose HBV vaccine. Additionally, 19 (6.4%) individuals tested positive for HBsAg and were counselled and referred to specialists from the University Hospital for further assessment and management. We found that 59 (19.9%) of our participants had previously initiated HBV vaccination and had taken at least one dose of the vaccine more than 6 months prior to this screening, 3 of whom tested positive for HBsAg. For the three-dose HBV vaccines deployed, a little over 20% (50/246) and a further 17% (33/196) did not return for the second and the third doses respectively, resulting in an overall 66% (163/246) of persons who completed all three vaccinations. Conclusions / Lessons learnt: Our medical campaign exercise established an active case prevalence rate of 6.4% and achieved a full vaccination success rate of 66% which is critical in the induction of long-term immunity in the participants. Aside these achievements, we would like to reiterate the importance of the use of different approaches including educational events and WHD activities to target groups and communities to raise awareness. Additionally, home and school vaccination programmes may be adopted to enhance vaccine uptake and adherence to the vaccination schedule. We plan to extend this screening exercise to deprived and/or rural communities where HBV incidence may be higher than in urban communities.